If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 7) = 21 Reorder the terms: 2(7 + x) = 21 (7 * 2 + x * 2) = 21 (14 + 2x) = 21 Solving 14 + 2x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 2x = 21 + -14 Combine like terms: 14 + -14 = 0 0 + 2x = 21 + -14 2x = 21 + -14 Combine like terms: 21 + -14 = 7 2x = 7 Divide each side by '2'. x = 3.5 Simplifying x = 3.5
| 8-4x=5(x-5) | | 0=x^2+2x+5 | | 1x-x= | | 5y-1=-17-3y | | 0.13(64)-0.33(8)= | | 2x-4-8= | | (1+j)(6-2j)= | | 6x+7(9-x)=61 | | 5x=6x-28 | | (4+3j)-(5j-6)= | | X^2+100=9x^2 | | 3(p^2-16p+81)=81 | | 12x^2-5x-3= | | 5x^2-8x-4= | | x+4=2x-1 | | 3k-3=2k+6 | | 5x+2=77 | | 54y-2y^3= | | 4x^2+28x-150=0 | | 12x^2-20x+3=0 | | 2x^2+30x+52= | | 4(2+j)-3(6+2j)+7j= | | 2(4x-7)=5(-2x-9)-5 | | 2g^2-14g+20=0 | | 4(x-2)=x-20 | | 3x-7=3x+5 | | 2(3x-1)=x+13 | | (x^2-4x+6)(2x^2+8x-1)=0 | | (x^2-4x+6)(2x^2+8x-1)=1 | | 9x+10=7x+2 | | -6y=d | | -6y=da |